Rancang Bangun Prototype Tap Changer Otomatis Berbasis IoT Menggunakan Transformator Satu Fasa Skala Laboratorium - Japriansyah, Dimas Aryo; Koerniawan, Tony; Rabbani, Arya Rambu; Fajar, Artyastu; Arasyid, Tsabit (Journal of Authentic Research, 2026)
Voltage fluctuations in distribution systems may cause service voltages to exceed standard limits, requiring transformer tap regulation mechanisms to maintain voltage stability. However, testing tap changers on full-scale distribution transformers involves safety risks, high costs, and limited flexibility for laboratory modifications. This study aims to design and evaluate an Internet of Things (IoT)-based tap changer prototype using a single-phase laboratory-scale transformer. The research employed an experimental design-and-development approach consisting of hardware design, software development, prototype assembly, and laboratory testing. The system comprises a single-phase transformer with five secondary-side tap positions, an ESP32 microcontroller, a PZEM-004T v3.0 sensor, a five-channel active-LOW relay module, and the Blynk platform for remote monitoring and control. Output voltage was measured every three seconds and used as the basis for tap selection within a voltage range of 198 V to 231 V. Testing was conducted using three types of loads: a 60 W incandescent lamp, a rheostat, and a combined incandescent lamp-rheostat load. The results show that Tap 2 to Tap 5 maintained output voltages within the acceptable range, while Tap 1 remained below the minimum standard limit under all load conditions. The maximum positive voltage deviation was +2.27% at Tap 5 under the incandescent lamp load, whereas the maximum negative deviation was -11.59% at Tap 1 under the combined load condition. The PZEM-004T sensor achieved an average relative error of 0.35% compared with a clamp power meter for voltage measurements. These findings indicate the preliminary feasibility of the proposed prototype as an IoT-based laboratory simulation and educational platform for transformer tap regulation, particularly under resistive loads and limited testing conditions. Further studies are required to evaluate system performance under inductive loads, dynamic voltage fluctuation scenarios, and long-term automatic control operation.